Experimental setup for studying the effect of dustiness in case of non-contact temperature measurements - N. S. Chernysheva; B. P. Ionov; A. B. Ionov (Омский научный вестник)
In this paper we present a laboratory installation for studying the effect of dustiness of the propagation medium in the case of non-contact temperature measurements. The presence of a nonstationary dust cloud in a real industrial environment between the object and the device of infrared thermal control is an important factor causing an additional error, which significantly distorts the measurement results. The article presents the results of experimental modeling of the base states of a dust cloud of clinker dust. The most informative signs of the estimation of these states are shown using the example of a five-channel pyrometer with spectral separation of channels and an optical particle counter. It is shown that the proposed experimental setup allows to adequately simulate various situations of a dusty state of space between the contactless temperature control device and the object of measurement.